Consistency test for surface electromyography during mastication hints different roles of masseter and anterior temporalis muscles - Sutiwisesak, Rujapope; Sotthiwat, Usanee; Phongratanadechachai, Siriwan; Dokmai, Traiphop; Seubbuk Sangkhamanee, Sujiwan; Tapechum, Sompol (Journal of Physiological and Biomedical Sciences, 2024)
Objectives: Sensorimotor adaptation is a neural process which continuously updates motor outputs in relation to sensation, including mastication which adapts from food textures and can be shown as patterns of muscle activation via electromyography (EMG). Yet, reliability of EMG on masticatory muscle activities have not been well documented. We designed a pilot study to confirm consistency of surface EMG activities across participants. Methods: Eight normal subjects and two food taster panelists were recruited. Surface EMG signals were recorded over bilateral anterior temporalis and masseter, right infrahyoid and digastric muscles while the participants chewed 8 sessions of each food sample. The samples included shrimp, sausage, carrot and soft gel, which was fabricated to demonstrate the sensorimotor adaptation during mastication. EMG signals were recorded and analyzed with PowerLab and LabChart8, respectively. Consistency of muscle activities was determined with intraclass-correlation coefficient. Unilateral domination of the muscles was determined by congruent domination on electrical activities (area under the curve; AUC) of both masseter and anterior temporalis. Results: We found that all of EMG parameters were consistent within participant, however few of them showed inconsistency across the population within a food sample. Gel sample showed unique muscle activity pattern. Unilateral deactivation of muscle activities was found with more profound in non-dominant masseter compared to non-dominant anterior temporalis. Conclusion: We have ascertained that surface EMG is a reliable tool to study sensorimotor adaptation of the masticatory muscles in response to food textures. Caution should be made in order not to select inconsistent parameter for data analysis. In addition, the difference in activities of anterior temporalis and masseter muscles suggest the distinct roles of each muscle on mastication.